2009
DOI: 10.1002/mawe.200800438
|View full text |Cite
|
Sign up to set email alerts
|

Zinc peroxide precursor for ZnO clusters

Abstract: Zinc peroxide is suggested as a new precursor for formation of zinc oxide clusters. (ZnO) n , n=1 -100 clusters have been produced by laser ablation of bulk powder of zinc peroxide and studied by time-of-flight mass spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…As the basis of the model, an isolated FL Zn32Al4O36 cluster was chosen to study its cohesive and electronic properties with different distribution of Al-O pairs [2,8], the defect formation energies of VZn [8], effect of intrinsic Oi defects [1], and packing defects on the electroactivity of the Al impurity in the ZnO lattice. Qualitative results for the behavior of Al impurity in FL cluster based on ZnO were obtained [8].…”
Section: Model and Computation Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…As the basis of the model, an isolated FL Zn32Al4O36 cluster was chosen to study its cohesive and electronic properties with different distribution of Al-O pairs [2,8], the defect formation energies of VZn [8], effect of intrinsic Oi defects [1], and packing defects on the electroactivity of the Al impurity in the ZnO lattice. Qualitative results for the behavior of Al impurity in FL cluster based on ZnO were obtained [8].…”
Section: Model and Computation Techniquementioning
confidence: 99%
“…The choice of such cluster as a model for ab initio quantum chemical study is due to the fact that isolated (ZnO)n clusters exist really and have been synthesized experimentally [2]. The information about formation of isolated clusters (ZnO)n, where n = 1 -100, was published in [2,3]. The authors reported that zinc oxide clusters have been processed by laser ablation of zinc peroxide in vacuum and investigated by time-of-flight (TOF) mass spectroscopy.…”
Section: Introductionmentioning
confidence: 99%